The Influence Of Taxpayer's Level Of Trust, Tax Knowledge Tax Education On Tax Payment Compliance Online Transaction In Surabaya - Selviana Nggole Wea; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
There are so many tax problems in Indonesia, especially online, with the passage of time, online buying and selling transactions will also increase and the level of difficulty is quite difficult to detect potential taxes online. Some of the descriptions above serve as the basis for conducting research by focusing on the factors that affect the level of taxpayer confidence, knowledge of taxation, tax counseling on compliance with online transaction tax payments in Surabaya. The population in this study are online actors in the fashion sector who operate on Instagram social media accounts and are domiciled in Surabaya. The analytical technique used in this study is Multiple Linear Regression. Based on the results of the analysis and discussion, the results of the study can be concluded as follows: The level of trust of taxpayers partially has a negative and insignificant effect on online tax payment compliance. Tax knowledge partially has a significant positive effect on online tax payment compliance. Tax counseling partially has a positive and insignificant effect on online tax payment compliance. There is a significant positive effect simultaneously on the level of taxpayer confidence, knowledge of taxation, tax counseling on tax payment compliance.